LGBT; nature or ideology: The view of a former LGBT practitioner in Malaysia - Owoyemi, Musa Yusuf; Ahmad Sabri, Ahmad Zaharuddin Sani (Medwell Publishing, 2013)
This research discusses the issue of LGBT in the Malaysian society by asking the view of a former practitioner of the sexual orientation described as LGBT. Using the qualitative method of interview and textual analysis of the interview, the research ask the question of whether this sexual orientation is a natural phenomenon or an ideology propagated by certain quarters as is the practice in the contemporary time. The findings of the research through the interaction with the former practitioner of this sexual orientation show that the issue is a double edge sword which requires caution and understanding from the larger society. However, the research shows that it is not something that is insurmountable as is being portrayed in certain quarters.